Shakespeare, Dissent and the Cold War - Thomas, Alfred. author. aut Link
X, 265 p.
Keywords: Shakespeare, Dissent and the Cold War is the first book to read Shakespeare's drama through the lens of Cold War politics. The book uses the Cold War experience of dissenting artists in theatre and film to highlight the coded religio-political subtexts in Hamlet, King Lear, Macbeth and The Winter's Tale.